Republic of Estonia : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper analyzes the drivers of wage growth and inflation in Estonia. The analysis reveals that the role played by the inflation and inflation expectations in Estonia is different from those of the EU15. The impact of inflation on wage formation is smaller than in larger and richer countries with lower inflation volatility. This has limited the downward pressure on wages during the period of very low inflation in 2014-16. Although there has been an episode of wage growth leading inflation before the global financial crisis, the current simultaneous acceleration in prices and wages is not evidence of a developing wage-price spiral, as a significant share of the increase in inflation is owing to exogenous factors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet